DYSTOCIA DUE TO ARTHROGRYPOSIS MULTIPLEX CONGENITA IN A GOAT - YADAV, y; JENA, B; CHAURASIA, D K; MISHRA, p c; DASH, D (The Indian Journal of Animal Reproduction, 2020)
A case of dystocia in an indigenous goat due to arthrogryposis multiplex congenita monster fetus with angulationof hock joint and kyphosis of dorsal spine was successfully removed by application of judicious manual traction.Key words: Congenital arthrogryposis, kyphosis, Monster, Goat.
Keywords: DYSTOCIA; ARTHROGRYPOSIS; GOAT